2015
DOI: 10.1017/s0952523815000036
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic connections of amacrine cells containing vesicular glutamate transporter 3 in baboon retinas

Abstract: The goals of these experiments were to describe the morphology and synaptic connections of amacrine cells in the baboon retina that contain immunoreactive vesicular glutamate transporter 3 (vGluT3). These amacrine cells had the morphology characteristic of knotty bistratified type 1 cells, and their dendrites formed two plexuses on either side of the center of the inner plexiform layer. The primary dendrites received large synapses from amacrine cells, and the higher-order dendrites were both pre- and postsyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Both glycine and glutamate are released in a Ca 2+ -dependent manner, indicating an underlying vesicular release mechanism, even though vIAAT was previously not immunolocalized to GACs (Haverkamp and Wassle, 2004; Johnson et al, 2004). Interestingly, the two co-released transmitters target separate postsynaptic GC circuits, suggesting most parsimoniously that glycine and glutamate are released from two separate populations of vesicles at different synapses, as also supported by a recent EM study which found both symmetric and asymmetric synapses on GAC processes in the primate retina (Marshak et al, 2015). …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Both glycine and glutamate are released in a Ca 2+ -dependent manner, indicating an underlying vesicular release mechanism, even though vIAAT was previously not immunolocalized to GACs (Haverkamp and Wassle, 2004; Johnson et al, 2004). Interestingly, the two co-released transmitters target separate postsynaptic GC circuits, suggesting most parsimoniously that glycine and glutamate are released from two separate populations of vesicles at different synapses, as also supported by a recent EM study which found both symmetric and asymmetric synapses on GAC processes in the primate retina (Marshak et al, 2015). …”
Section: Discussionmentioning
confidence: 61%
“…Recently, it was discovered that a special subclass of amacrine cell, which is immunoreactive to vesicular glutamate transporter 3 (vGluT3) (Fremeau et al, 2002; Gong et al, 2006; Haverkamp and Wassle, 2004; Johnson et al, 2004; Stella et al, 2008), releases glutamate and makes excitatory synapses onto specific GC types (Krishnaswamy et al, 2015; Lee et al, 2014). These glutamatergic amacrine cells (GACs) have also been found to be immunoreactive to glycine and glycine transporter GlyT1 (but not vesicular inhibitory amino acid transporter, vIAAT) (Haverkamp and Wassle, 2004; Johnson et al, 2004), raising an intriguing possibility that GACs may release glycine in addition to glutamate (Marshak et al, 2015), even though functional glycine-glutamate co-release has not been reported in the mature nervous system. In order to test this possibility and gain a functional insight into a potential glycine-glutamate co-transmission system, one needs to determine (1) whether GACs release glycine under physiological conditions, and if they do, (2) whether the release is through a vesicular mechanism, (3) whether GACs release glycine and glutamate onto the same or different postsynaptic targets, and (4) what specific synaptic circuits and functional advantages may be subserved by such inhibitory-excitatory co-transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Amacrine synapses were identified in electron microscopy studies based on the absence of ribbons (Calkins et al, 1994). MGCs could receive non-ribbon excitatory contacts, e.g., from glutamatergic amacrine cells (Lee et al, 2014; Marshak et al, 2015), and bipolar cells could make some conventional synapses on the dendrites of MGCs (Kolb and Dekorver, 1991). The MGC is contacted by a single midget bipolar cell with a claw-like synaptic terminal containing 25–50 ribbons (Calkins et al, 1994) packed into a small volume (~70 μm 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The unlabeled profiles were identified by their characteristic ultrastructure [22]. The criteria for evaluating labeled synapses were described in detail recently [23]. The sample included 436 synapses, including approximately equal numbers from each of the strata of the IPL in which labeled dendrites were found (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…These include: diffuse cells [39], knotty type 2 cells [40], A8 cells [11] and several other knotty amacrine cell types that are known only from retinas labeled with the Golgi method [19]. Amacrine cells that contain vesicular glutamate transporter 3 are also glycinergic, but because they are not labeled by antisera to GlyT-1 [23], they did not account for any of the profiles observed in this study.…”
Section: Discussionmentioning
confidence: 99%